The role of myeloid-derived suppressor cells in chronic infectious diseases and the current methodology available for their study. Issue 5 (27th November 2018) - Peñaloza, Hernán F; Alvarez, Diana; Muñoz-Durango, Natalia; Schultz, Bárbara M; González, Pablo A; Kalergis, Alexis M; Bueno, Susan M
Abstract: An effective pathogen has the ability to evade the immune response. The strategies used to achieve this may be based on the direct action of virulence factors or on the induction of host factors. Myeloid-derived suppressor cells (MDSCs) are immune cells with an incredible ability to suppress the inflammatory response, which makes them excellent targets to be exploited by pathogenic bacteria, viruses, or parasites. In this review, we describe the origin and suppressive mechanisms of MDSCs, as well as their role in chronic bacterial, viral, and parasitic infections, where their expansion seems to be essential in the chronicity of the disease. We also analyze the disadvantages of current MDSC depletion strategies and the different in vitro generation methods, which can be useful tools for the deeper study of these cells in the context of microbial infections. Graphical Abstract: Myeloid-derived suppressor cells, their mechanisms to suppress the immune response during bacterial, viral, and parasitic infections and current methodologies to study them.